Carotid Cavernous Fistula during Thrombectomy for Acute Ischemic Stroke: A Case Report - Ogawa, Nobuhiro; Nozaki, Kazuhiko; Tsuji, Keiichi; Tsuji, Atsushi; Yoshimura, Yayoi; Nakazawa, Takuya (Journal of Neuroendovascular Therapy, 2021)
Objective: We report a rare complication, carotid cavernous fistula (CCF), due to vessel perforation during thrombectomy for acute ischemic stroke (AIS).Case Presentation: An 88-year-old woman underwent thrombectomy for left C4 occlusion of the internal carotid artery. There was strong resistance at the medial C4 while the microguidewire was guided distally, and a CCF was found after deploying and retrieving the stent. It was thought to have been caused by perforation due to intracranial atherosclerotic stenosis of the internal carotid artery.Conclusion: During thrombectomy for intracranial large vessel occlusion underlying intracranial atherosclerotic stenosis, the risk of vascular injury should be kept in mind.